Flexible simulations of complex networks in OpenStack clouds. (2017) - Costanzo, Francesco; Messina, Fabrizio; Pappalardo, Giuseppe; Santoro, Corrado
This paper describes a flexible software architecture aimed at performing simulations of complex networks on cloud computing environment based on OpenStack. The kernel of the architecture consists of ComplexSim, a C-based software simulator of complex networks composed of two different layers: the Parallel Simulation Kernel is devoted to manage event-driven simulations on SMP systems through a set of API calls useful to schedule tasks and events; on the other hand, API of the Complex Network Data & Runtime is used to define the complex network in terms of the graph of entities and related user-defined attributes, as well as the runtime behaviour. Two additional components provide the necessary automation to configure, deploy and execute a set of simulations in OpenStack clouds: the Cs-Generator allows to generate any set of user-defined directives, as well as directives for the engine; Cs-CloudRuntime is the component devoted to run the user-defined set of simulations in an OpenStack cloud, i.e. VMs preparation, deployment and execution, as well as collection of results.